2018
DOI: 10.1007/s00066-018-1347-6
|View full text |Cite
|
Sign up to set email alerts
|

Alterskorrigierter Hörverlust nach Radiochemotherapie bei Patientinnen mit Zervixkarzinom

Abstract: Chemoradiation with cumulative cisplatin doses up to 400 mg did not lead to significant impairment of objective or subjective hearing. For cervical cancer patients undergoing chemoradiation, standard audiometry is not indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
1
7
2
Order By: Relevance
“…In terms of hearing perception alteration, the current results of the study show that less than half of patients worry about altered hearing perception, which is consistent with (Marnitz et al, 2018) and (Noszek et al, 2017) The current findings agree with Monfort et al, (2017) that cancer patients who receive ACH often experience falls and unstable gait. In addition, the research of Espy, Yang, Bhatt, & Pai, (2010) who showed that cancer patients often experience walking problems, feeling shaky, and having a decreased sense of balance, possibly affecting their ability to perform daily living tasks.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of hearing perception alteration, the current results of the study show that less than half of patients worry about altered hearing perception, which is consistent with (Marnitz et al, 2018) and (Noszek et al, 2017) The current findings agree with Monfort et al, (2017) that cancer patients who receive ACH often experience falls and unstable gait. In addition, the research of Espy, Yang, Bhatt, & Pai, (2010) who showed that cancer patients often experience walking problems, feeling shaky, and having a decreased sense of balance, possibly affecting their ability to perform daily living tasks.…”
Section: Discussionsupporting
confidence: 91%
“…Cisplatin is one of the most widely used anticancer drugs in the treatment of a variety of malignant tumors. It is also the most ototoxic drug in clinical use, causing permanent hearing loss in approximately 50% of treated patients [308][309][310][311][312]. A recent study showed that atorvastatin significantly reduced the incidence and severity of cisplatin-induced hearing loss [313].…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%
“…Many individuals treated with cisplatin experience significant toxicities, including nephrotoxicity, neurotoxicity, myelosuppression, and ototoxicity. Over 50% of patients who undergo cisplatin therapy acquire a sensorineural hearing loss (3)(4)(5)(6)(7), which compromises daily communication with friends, family, and health care providers and can lead to loneliness, social isolation, and frustration (8). Cisplatin-induced hearing loss is permanent, and there are currently no FDA-approved therapies to reduce or prevent cisplatin ototoxicity.…”
Section: Introductionmentioning
confidence: 99%